Microbial analysis and determination of antibiotic susceptibility of dental laboratory equipments and laboratory attire - Manoj Shetty; Nikhila Thulasidas; Nivya John; Chethan Hegde (Wolters Kluwer Medknow Publications, 2018)
Context: This study was done to determine the level and type of microbial contamination present on the surface of various dental laboratory equipment and laboratory attire and to determine the antibiotic susceptibility pattern of these isolated pathogens. Subjects and Methods: The samples were divided into following groups: six groups of dental laboratory equipment (articulators, facebow, fox plane, polishing buff, micromotor handpiece, and surveyors) and dental attire of laboratory technicians and students. A total of 33 swabs were collected from each dental laboratory equipment, namely, articulators, facebow, fox plane, polishing buff, micromotor handpiece, and surveyors. The dental laboratory attire of students and dental technicians were analyzed separately. The swabs were collected from the laboratory attire at the end of the week, and they were washed once a week and at the beginning of the week. The groups are Group 1 - dental laboratory attire (students), Group 2 - dental laboratory attire (technicians), Group 3 - polishing buff, Group 4 - facebow, Group 5 - surveyor, Group 6 - fox plane, Group 7 - articulator, and Group 8 - micromotor handpiece. The moistened swabs were inoculated into the broth and subcultured on to the MacConkey Agar plates, and then incubated aerobically at 37°C for 24 h. The organisms were identified based on colony morphology, Gram staining, and standard biochemical tests. The antibiotic susceptibility patterns of the isolated organisms were done according to the CLSI guidelines. The collected data were statistically analyzed. Statistical Analysis Used: The data collected were entered into a Microsoft Excel Spreadsheet and analyzed using IBM SPSS Statistics, Version 22 (Armonk, NY, IBM Corp.). The frequency and mean standard deviation of the samples were analyzed using Fisher's exact value test. Percentage of resistance among the isolates to different antimicrobials was also determined. Results: The microorganisms isolated were Staphylococcus aureus, Escherichia coli, coagulase-negative Staphylococcus, Pseudomonas, Klebsiella, nonfermenting Gram-negative bacteria, and Bacillus species. The mean microbial levels in dental laboratory attire were more (5 log10colony-forming units [CFU]) compared with dental equipment (3 log10CFU-4 log10CFU). Furthermore, most of the isolated organisms showed increased antimicrobial resistance. Conclusion: Majority of the isolated organisms were not a part of the normal oral microflora and are capable of causing various diseases. The increased resistance to the antimicrobials showed by the isolated organisms proves that there are increased chances of multiresistant organisms to occur in the future.